Carcass and beef quality of crossbred cattle fed increasing linseed oil levels - Rosa, Bruna Laurindo; Oliveira, Emanuel Almeida de; Henrique, Wignez; Pivaro, Thiago Martins; Mota, Diego Azevedo; Messias, Cassio Toledo; Marchi, Patrícia Gelli Feres de; Silva, Lidianne Assis; Araújo, Danielle Saldanha de Souza (Semina: Ciências Agrárias, 2021)
Strategies to improve beef nutritional value, mainly fatty acid composition, have been a major goal for the scientific community. The use of different oil contents, mostly those rich in unsaturated fatty acids, can be interesting for cost reduction, as well as cattle performance and meat quality improvements. This study assessed the influence of diets containing increasing linseed oil levels (1.0, 3.8, and 5.2% DM) on performance, carcass traits, and meat quality of feedlot-finished Nellore x Canchim steers and heifers. The experiment was carried out in a randomized block design and arranged in a mixed 3 x 2 factorial scheme. Increasing oil levels linearly decreased dry matter intake (DMI) (P < 0.05) and hence improved feed efficiency (P < 0.05), regardless of sexual condition. A beneficial effect of increasing the inclusion of linseed oil was the reduction DMI. Steers had a higher weight at slaughter (P < 0.05) and heifers had greater backfat thickness (P < 0.05). The concentrations of most fatty acids were changed by the linseed oil levels studied (P < 0.05). Dietary inclusion of linseed oil improved beef quality by reducing (P < 0.05) the n-6:n-3 ratio by 1.3 points per percentage point increase in linseed oil level in the finishing diet of both sexes.